2019
DOI: 10.1002/ppp.2008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of rock glaciers and permafrost distribution in Uttarakhand, India

Abstract: We have compiled an inventory of 1004 rock glaciers for Uttarakhand State, India, using high‐resolution satellite data freely available on Google Earth. The inventory is used to analyze the origin, spatial distribution, geometry and dynamics of rock glaciers using a combination of optical remote sensing techniques with a geographic information system (GIS). Results show that development of rock glaciers in this region depends strongly on high elevation (> 4000 m a.s.l.) and slope aspect. Rock glaciers are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 74 publications
1
31
0
Order By: Relevance
“…Figure S3 also illustrates the clustering of rock glaciers around northerly aspects. The results presented here corroborate the findings of other northern hemisphere studies, which have detailed similar relationships 20,[31][32][33] , . Therefore, it is reasonable to assume that northerly aspects with their reduced solar insolation enable rock glacier formation and preservation at lower elevations than other aspects, in particular, southerly aspects.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Figure S3 also illustrates the clustering of rock glaciers around northerly aspects. The results presented here corroborate the findings of other northern hemisphere studies, which have detailed similar relationships 20,[31][32][33] , . Therefore, it is reasonable to assume that northerly aspects with their reduced solar insolation enable rock glacier formation and preservation at lower elevations than other aspects, in particular, southerly aspects.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, while systematic rock glacier inventory coverage has increased globally, HMA is comparatively datadeficient 12 . Across HMA, with few exceptions [19][20][21] , rock glacier inventories have been conducted at localised sites, over relatively small spatial scales or are not spatially explicit [22][23][24] . Therefore, the distribution and hydrological significance of rock glaciers remains unknown.…”
mentioning
confidence: 99%
“…Previous studies have successfully applied GEOtop in mountain regions e.g. simulating snow depth (Endrizzi et al, 2014), snow cover mapping (Dall'Amico et al, 2011bEngel et al, 2017;Zanotti et al, 2004), ecohydrological processes (Bertoldi et al, 2010;Chiesa et al, 2014), modelling of ground temperatures in complex topography (Bertoldi et al, 2010;Endrizzi et al, 2014;Fiddes and Gruber, 2012;Gubler et al, 2013), water and energy fluxes (Hingerl et al, 2016;Rigon et al, 2006;Soltani et al, 2019), evapotranspiration (Mauder et al, 2018), and permafrost distribution (Fiddes et al, 2015).…”
Section: Modelling Of Surface Energy Balancementioning
confidence: 99%
“…In the Indian Himalayan Region (IHR), recent studies show that the discontinuous permafrost can be found between 3000 and 5500 m a.s.l. (Allen et al, 2016;Baral et al, 2019;Pandey, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While the GT data set with a large number (1,061) of samples is representative in most of the TP, the sample sites are relatively inadequate with most (96.1%) measurements in areas with slope angle <20°. The RG datasets are from Jones, Harrison, Anderson, Selley, et al (2018) and Baral et al (2020). These were derived based on image interpretation in Google Earth by professional technicians.…”
Section: Study Area and Inventory Of Permafrost Presence Or Absencementioning
confidence: 99%